PENGARUH KOMBINASI SORGUM DAN KACANG TUNGGAK TERFERMENTASI TERHADAP SIFAT FISIK DAN ORGANOLEPTIK SERBUK MINUMAN SEREALIA - Ulfa, Masayu Nur; Ramanda, Muhammad Rizky; Nurfadillah, Nurfadillah (Jurnal Gizi dan Pangan Soedirman, 2025)
Stunting caused by malnutrition from the prenatal period to the age of two can cause various short-term and long-term health problems. One solution to prevent malnutrition is providing additional food (PMT) from local ingredients. Therefore, this study utilized sorghum and cowpeas, which are high in carbohydrates and protein and are expected to prevent malnutrition in pregnant women and toddlers. Additionally, they maximize local food ingredients such as cereal drink powder. This study aimed to determine the effect of the combination of sorghum and cowpeas on the physical and organoleptic characteristics of cereal drink powder. This study used a Completely Randomized Design (CRD) with the addition of sorghum and cowpea at concentrations of 15%: 15%, 20%: 10%, and 25%: 5%, with two repetitions, each in duplicate. Data were analyzed using one-way ANOVA at a 5% significance level, and if significant differences were found, DMRT was used for further analysis. The results showed that the concentration of sorghum and cowpeas had a significant effect (p<0.05) on viscosity, rehydration time, color, and organoleptic attributes (taste, thickness, and overall). However, the concentration did not have a significant effect (p>0.05) on hygroscopicity rate, hygroscopicity level, solubility, and organoleptic attributes (color and aroma).